Relación entre la puntuación de riesgo de diabetes finlandesa y el perfil lipídico en Ecuador. Estudio de corte transversal - Rivadeneira-Dueñas, Josué; Fuenmayor-González , Luis; Flores-Lastra, Nancy; Herrera-Jumbo , Pablo; Jácome-García, Michelle; Castillo, Luz; Tello-Cañar , Raisa; Guerra-Tello , María José; Fajardo-Loaiza , Thalía; Alarcón-Roa , Javier; Lara-Salas , Nicolás (Revista de la Facultad de Ciencias Médicas (Quito), 2025)
Introduction: Non-communicable diseases such as type 2 diabetes mellitus and dyslipidemias are highly prevalent in Ecuador. The Finnish Diabetes Risk Score (FINDRISC) measures the 10-year risk of developing diabetes, but its relationship with lipid profile has not been studied locally. This study examined the relationship between FINDRISC test results and total, HDL, and LDL cholesterol levels in Ecuadorian primary care patients. Objective: Analyze the relationship between the FINDRISC test score and lipid profile parameters in patients treated at primary care centers in Ecuador. Methods: A cross-sectional study was carried out in 236 adults without diabetes. The FINDRISC test score was calculated, and clinical and biochemical data were collected. Nonparametric tests were used to analyze correlations and differences between risk groups. Results: A moderate or higher risk of diabetes was present in 37.3% of participants. There were significant positive correlations between the FINDRISC score and both LDL (rho=0.37; p<0.001) and total cholesterol (rho=0.16; p=0.01). Intergroup differences were noted (p=0.04), but there was no correlation with HDL. Discussion: A higher FINDRISC score is associated with increased levels of total cholesterol and LDL, suggesting the tool may be useful for identifying broader metabolic risks beyond diabetes alone. While these findings align with existing research, the study's cross-sectional design and non-probabilistic sampling limit the ability to establish causality and generalize the results to the wider population. Conclusion: Higher LDL and total cholesterol levels are linked to increased FINDRISC scores. These findings support using the FINDRISC tool in primary care to identify broader metabolic risk